(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
The series of papers published under the title Perspectives on Chinese Law presents the main features of China’s legal landscape today. The first paper describes the Chinese legal reforms from 1978 to the present day, modernization and tradition in Chinese legal culture, Chinese legal education and the Chinese Judiciary.